2012
DOI: 10.1001/archgenpsychiatry.2011.1561
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk in Primary Care Patients With Major Physical Diseases

Abstract: Our findings indicate that clinical depression is a strong confounder of increased suicide risk among physically ill people. They also demonstrate an independent elevation in risk linked with certain diagnoses, particularly among women. Health care professionals working across all medical specialties should be vigilant for signs of undetected psychological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
149
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 52 publications
15
149
2
4
Order By: Relevance
“…As hypothesised, the APMS participants with multimorbidity exhibited higher risks of suicidal thoughts compared to those with neither physical health nor CMD conditions and, as such, our results support some previous studies on the role of mental and physical illness in suicide risk (Qin et al, 2014;Qin et al, 2013;Ratcliffe et al, 2008;Webb et al, 2012). In a population-based study in Canada, Bolton and colleagues concluded that when mental illness was taken into account, cancer patients compared to patients with other chronic illness had an increased suicide risk 3 months following cancer diagnosis (Bolton et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As hypothesised, the APMS participants with multimorbidity exhibited higher risks of suicidal thoughts compared to those with neither physical health nor CMD conditions and, as such, our results support some previous studies on the role of mental and physical illness in suicide risk (Qin et al, 2014;Qin et al, 2013;Ratcliffe et al, 2008;Webb et al, 2012). In a population-based study in Canada, Bolton and colleagues concluded that when mental illness was taken into account, cancer patients compared to patients with other chronic illness had an increased suicide risk 3 months following cancer diagnosis (Bolton et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, studies on suicide deaths of people with physical illness diagnoses appear to have an increased prevalence of mental disorders (Henriksson et al, 1995;Qin et al, 2014;Webb et al, 2012). Chronic illnesses like cancer, asthma, musculoskeletal and cardiovascular disease may play a role in the development of suicidal behaviours, varying as a function of the presence of subsequent mental disorder (Bolton et al, 2015;Webb et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between these two groups regarding a self-reported lifetime history of suicide attempts was even more pronounced and significant (15.0% for COPD patients, 6.6% for subjects without COPD; OR52.29). According to a large case-control study [44] the relative risk of suicide was significantly elevated among patients with COPD compared with patients without major chronic illnesses (3.1% versus 1.9%, respectively; OR51.80).…”
Section: Suicidality In Patients With Copdmentioning
confidence: 99%